E‐cigarette or vaping product use‐associated lung injury (EVALI) features and recognition in the emergency department. Issue 5 (8th June 2020) - Aldy, Kim; Cao, Dazhe James; Weaver, Mary Madison; Rao, Devika; Feng, Sing‐Yi
Abstract: Since August 2019, the pulmonary disease termed e‐cigarette or vaping product‐use associated lung injury (EVALI), has resulted in 2758 hospitalizations and 64 deaths in the United States. EVALI is considered in patients who have vaped or dabbed within 90 days of symptom onset, and have abnormal lung imaging in the absence of any pulmonary infection. The majority of EVALI patients are otherwise healthy adolescents and young adults. The leading etiology of EVALI is contamination of delta‐9‐tetrahydrocannabinoid (THC) e‐liquids with vitamin E acetate. Although the exact pathophysiology of vitamin E acetate‐induced lung injury is unknown, vitamin E acetate may lead to pulmonary lipid accumulation and/or interfere with surfactant functioning. EVALI symptoms are vague but consist of a constellation of constitutional, pulmonary, and gastrointestinal symptoms. Patients often present multiple times to healthcare facilities as their clinical condition worsens with a considerable mortality risk. The diagnosis of EVALI hinges on obtaining history leading to the recognition of vaping/dabbing. Physicians need to be persistent, but nonjudgmental, in obtaining vaping histories, especially in THC‐prohibited states. Radiographical findings of nonspecific bilateral ground‐glass infiltrates are best detected on computed tomography. Management for EVALI requires a multidisciplinary approach focused on supportive respiratory care and ruling‐out infectious causes. Corticosteroids may be of benefit. Most patients who are hypoxic, have comorbidities, or lack appropriate follow‐up within 24–48 hours should be admitted for monitoring. Patients may benefit from substance abuse counseling and should be instructed to avoid vaping. As the outbreak continues, cases should be reported to local health departments and poison control centers.